Ethical Considerations for Using Artificial Intelligence in Digital Technologies - William Jorgensen; Matt Bjornsen; Rikke Carlsen (International Journal of Ethics and Society)
Introduction: The widespread penetration of artificial intelligence technology in various aspects of human life raises major concerns regarding the degree to which these technologies adhere to ethical standards. Therefore, the aim of the present study is to identify key ethical concepts for using artificial intelligence in digital technologies.